Prototype of Health Education to Improve the Quality of Life of Students with Scoliosis - Andrew Wijaya Saputra; Dela Fariha Fuadi; Putri Karina Syafitri; Cicilia Febriani Hayuningrum; Nesi; Wa Ode Rantika; Adella Faradilla; Danisa Nurul Fatimah; Suryo Ramadan (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: Adolescent idiopathic scoliosis (AIS) is a malalignment vertebra that occurs in adolescence and develops at 11 – 18 years old. This condition could worsen due to poor posture habits and heavy load on one side during daily activities. This study aims to examine whether the prototype health education impacted the quality of life of students with scoliosis. Methods: This research used quasi-experimental with pre-test and post-test design. This study's population was all Public Junior High School students in 289 Jakarta. Moreover, a purposive sampling technique was used. Fifteen students participated and completed all the interventions. The participant conducted a posture assessment using a postural grid, and then the degree of the spine curve was measured using a scoliometer, and the pain was measured by the Visual Analog Scale (VAS). For evaluation, it will focus on knowledge about scoliosis, posture, pain level, and quality of life. Results: The Wilcoxon test shows significant differences between before and after the intervention on the knowledge (p<0.001; z = -3.535), degree of scoliosis (p<0.5; z = -2.264), pain level (p<0.5; z = -2.232 ), and quality of life scores (p<0.01; z = -2.848). A pre-test and post-test correlation test was carried out using the Spearman test. There was a correlation between pain and the student's quality of life (r=0.551). Conclusion: The prototype in this study could improve knowledge significantly but did not significantly improve students' quality of life. However, it showed that reducing pain could improve the quality of life for students with scoliosis.